GIVING RESPONSE GNRH HORMONE, ESTROGEN, PROGESTERONE AND PROSTAGLANDIN IN ESTRUS SYNCHRONIZATION IMPLEMENTATION ESTROUS COW RECIPIENT FRIESIAN HOLSTEIN - Kurniawan, Sukurna; Handarini, Ristika; dihansih, elis (Jurnal Peternakan Nusantara, 2019)
This study aimed to test the effectiveness of the injection of a combination hormone GnRH, estrogen, progesterone and prostaglandin on response of estrus, onset estrus and duration estrus FriesianHolstain (FH) recipient dairy cattle. This study was used 15 recipient cows not pregnant, were divided into three treatment methods of synchronization of estrus and each treatment consisted of 5 cattle. Recipient cow estrus response after injection of the hormone combination estrus synchronization with all three treatments show symptoms of estrous. The percentage of estrous cows FH overall recipient reaches 100%, showed that the treatment effect is very good and effective way to bully the onset of estrous cows recipient FH. The results of data analysis using Chi-Square showed no significant difference among all treatments. It was concluded, that synchronization of estrous FHcow recipients using GnRH hormone, estrogen, progesterone and prostaglandin as good in all of the parameters. Keywords: estrous synchronization, GnRH, estrogen, progesterone, prostaglandin.